Analyzing Fit Mediation in The Tourism Marketing Strategy: The Influence of Risk Perception Toward Tourist Behavior - Noveri Maulana (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study examines a behavioral model for tourists, focusing on risk perception, satisfaction, revisit intention, and word-of-mouth (WoM) intention as the core constructs shaping tourism dynamics in the post-pandemic recovery period. Primary data were collected via a questionnaire-based survey of 568 domestic and international tourist respondents visiting Indonesia during the initial transition toward an endemic phase. Data analysis was conducted using Structural Equation Modeling (SEM) to test both direct and indirect relationships among variables and to verify the proposed model's validity. The findings reveal that risk perception has a significant and negative influence on tourist satisfaction. Furthermore, applying the 'Fit as Mediation' conceptual framework, this research confirms that satisfaction acts as a full mediating variable in the relationship between risk perception and behavioral loyalty that operationalized through revisit and WoM intentions. These results underscore that, within the context of a post-global health crisis, effective risk mitigation strategies must not only aim to reduce negative perceptions but should also be concurrently directed at enhancing experiential quality and tourist satisfaction to foster long-term loyalty. The theoretical and practical implications of this study are discussed for tourism industry stakeholders.